The effect of health on refugees' labor market integration: Evidence from a natural experiment in Germany - Laura Goßner; Philipp Jaschke; Yuliya Kosyakova (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2025)
This paper analyzes the role of health for refugees' integration into host societies' labor markets. We exploit the quasi-random dispersal policies of refugees across regions in Germany to analyze the causal effect of health on employment. Based on regional and temporal heterogeneity in a policy adoption that provided earlier access to health care services through electronic health cards (eHCs), combined with the regional availability of health care services and pre-migration health status, we construct instrumental variables (IVs) providing plausibly exogenous variation in refugees' post-arrival health status. Our results reveal that favorable physical health (PCS) improves males' employment probability. Concurrently, favorable mental health (MCS) increases females' employment rates, although this effect must be scrutinized due to weak instruments. Regarding potential mechanisms, we provide evidence that better health increases language course participation and German language proficiency for female refugees. – – Dieses Papier analysiert die Rolle der Gesundheit für die Arbeitsmarktintegration von Geflüchteten in ihrem Zielland. Wir nutzen die quasi-zufällige anfängliche regionale Verteilung von Geflüchteten über Stadt- und Landkreise in Deutschland, um den kausalen Effekt der Gesundheit auf die Beschäftigung zu analysieren. Basierend auf regionaler und zeitlicher Heterogenität bei der Einführung einer Reform, die einen früheren Zugang zu Gesundheitsleistungen durch elektronische Gesundheitskarten (eGKs) ermöglichte, in Kombination mit der regionalen Verfügbarkeit von Gesundheitsdienstleistungen und dem Gesundheitszustand vor der Migration, konstruieren wir Instrumentalvariablen (IVs), die plausibel exogene Variationen im Gesundheitszustand der Geflüchteten nach ihrer Ankunft liefern. Unsere Ergebnisse zeigen, dass ein guter körperlicher Gesundheitszustand (PCS) die Erwerbstätigkeitswahrscheinlichkeit von Männern verbessert. Gleichzeitig erhöht ein guter psychischer Gesundheitszustand (MCS) die Erwerbstätigenquote von Frauen, wobei dieser Effekt aufgrund schwacher Instrumente mit Vorsicht zu betrachten ist. Hinsichtlich möglicher Mechanismen zeigen wir, dass eine bessere Gesundheit die Teilnahme an Sprachkursen und die deutschen Sprachkenntnisse von weiblichen Geflüchteten erhöht.
Keywords: C26; I10; I18; J64; 330; electronic health card; employment; health; IAB-BAMF-SOEP survey of refugees; MCS; PCS; refugees